AMNESTY PROGRAMME, ENABLING LAWS AND SUSTAINABLE DEVELOPMENT IN NIGER DELTA OF NIGERIA - Dike, Samuel Chisa; Toby, Boma Geoffrey; Amaramiro, Ahamefula Steven (PEOPLE: International Journal of Social Sciences, 2021)
The Niger Delta Region remains the greatest wetland and resource region in Africa; it is rich in renewable, non-renewable, natural, terrestrial, and aquatic lives and human resources located within the Gulf of Guinea in the Atlantic Ocean. The environment and ecology support major economic activities which accounts for over 60% of the oil production and export since 1958. However, the export revenue and foreign exchange received in return have not translated equitably to the development of the region thus the ugly scenario engendering anger, distrust particularly against the federal government of Niger and culminating in the struggle, destruction, economic strangulation, and degradation that play out in the region. Efforts to douse the ensuing tensions and brewing crises from the region resulted in the amnesty programme. This paper evaluates the region; its resources, amnesty programme, and laws aimed at setting the region on the path of sustainable development. The objective is to find a relationship between the existing resources and the acclaimed development of the region to see how the extant laws have promoted and sustained empowerment in the region. A serious disconnect between the people, their resources, and sustainable development is discovered. The conclusion is that the existing legal frameworks have not yielded the much-required impact and recommend the enactment of some laws that will promote sustainable peace and enduring development.